Spatiotemporal trends in daily and subdaily rainfall extremes and return levels in Turkey. (22nd November 2022) - Albayrak, Derya; Sen, Omer Lutfi; Yucel, Ismail
Abstract: In this study, we present the long‐term daily and subdaily station data of annual extreme rainfall (1970–2015) and the trend analyses in rainfall regimes in Turkey. Trends in 5, 10, 15, and 30 min, 1, 2, 6, 12, and 24 hr of extreme rainfall in seven different rainfall regimes are estimated through nonparametric tests. The trends in return levels (2, 20, and 100 years) are defined by an appropriate three‐parameter generalized extreme value distribution and are evaluated in the climatological context of rainfall regimes. Overall, from 5‐min to 2‐hr durations, magnitudes of trends in extreme rainfall constantly increase in all rainfall regimes, which may be attributed to the intensified contribution of convective rainfall as a response to warming. Trend analysis of return levels reveals that, compared with 2‐year return levels, low‐probability high‐impact extreme rainfall events generally have the lowest estimated median trends until 30‐min to 2‐hr range. A shift in the magnitudes of trends occurs generally at 30‐min and 1‐hr durations; trends of rare intense events increase at the expense of less intense extreme rainfall. Thus, the intensification of 1–2‐hr extreme rainfall events can arise from both the increasing trends of more common events in shorter rainfall durations and from the increase in the trends of low‐probability high‐impact extreme rainfall events at this range. Moreover, explicitly in continental rainfall regimes, increases in the magnitudes of the trends in 30‐min to 2‐hr duration range are accompanied by various declines in 6–24‐hr duration range. Although coastal regimes generally have increasing trend values from 5‐min to 24‐hr durations, in northern and southern clusters, changes occur in the variability of extreme rainfall and the trend values of rarer (20‐ and 100‐year return periods) extreme rainfall exhibit increases in 6–12‐hr range. Abstract : The spatiotemporal evaluation of daily and subdaily extreme rainfall indicates vulnerabilities in critical infrastructure. From 5‐min to 2‐hr durations magnitudes of trends in extreme rainfall constantly increase in all rainfall regimes. In 30‐min to 1‐hr duration range, trends of 20‐ and 100‐year return levels tend to surpass the trends of 2‐year return levels. Northern and southern coastal regimes have the highest trend values for 20‐ and 100‐year return levels at 6 and 12‐hr durations of extreme rainfall.